2023
DOI: 10.1007/s44154-023-00127-9
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of strigolactones improves the desiccation tolerance, grain yield and water use efficiency in dryland wheat through modulation of non-hydraulic root signals and antioxidant defense

Sha Guo,
Xiaofei Wei,
Baoluo Ma
et al.

Abstract: Non-hydraulic root signals (nHRS) are affirmed as a unique positive response to soil drying, and play a crucial role in regulating water use efficiency and yield formation in dryland wheat production. Strigolactones (SLs) can enhance plant drought adaptability. However, the question of whether strigolactones enhance grain yield and water use efficiency by regulating nHRS and antioxidant defense systems in dryland wheat remains unanswered. In this study, pot experiments were conducted to investigate the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…However, when GR24 was added to the NaCl treatment, the activity of these enzymes remarkably increased, and the expression levels of their corresponding genes were upregulated compared to untreated plants. Moreover, a study on wheat plants subjected to drought stress revealed that the activities of antioxidant enzymes, particularly SOD and APX, increased significantly when the soil water content dropped to 50% of field capacity (FC), which was higher in GR24-treated plants [96]. This suggests that a higher antioxidant defense capacity is an essential mechanism through which exogenous GR24 can alleviate oxidative stress and improve stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…However, when GR24 was added to the NaCl treatment, the activity of these enzymes remarkably increased, and the expression levels of their corresponding genes were upregulated compared to untreated plants. Moreover, a study on wheat plants subjected to drought stress revealed that the activities of antioxidant enzymes, particularly SOD and APX, increased significantly when the soil water content dropped to 50% of field capacity (FC), which was higher in GR24-treated plants [96]. This suggests that a higher antioxidant defense capacity is an essential mechanism through which exogenous GR24 can alleviate oxidative stress and improve stress tolerance.…”
Section: Discussionmentioning
confidence: 99%